Saving private e-mail. - Vaughan-Nichols, S.J (IEEE spectrum)
In the spam war trenches, clever programmers are trying to stem the tide of unwanted messages. A powerful and effective new filtering method has started to emerge. The new strategies draw on techniques of probability theory originally invented by Thomas Bayes, the 18th century mathematician, to analyze entire e-mail messages instead of just the words that jump out.